Analytical evaluation of different carbon sources and growth stimulators on the biomass and lipid production of Chlorella vulgaris – Implications for biofuels. (April 2015) - Josephine, A.; Niveditha, C.; Radhika, A.; Shali, A. Brindha; Kumar, T.S.; Dharani, G.; Kirubagaran, R.
Abstract: The key challenges in lipid production from marine microalgae include the selection of appropriate strain, optimization of the culture conditions and enhancement of biolipid yield. This study is aimed at evaluating the optimal harvest time and effect of chlorella growth factor (CGF) extract, carbon sources and phytohormones on the biomass and lipid production in Chlorella vulgaris . CGF, extracted using hot water from Chlorella has been reported to possess various medicinal properties. However, in the present study, for the first time in C. vulgaris, CGF was found as a best growth stimulator by enhancing the biomass level (1.208 kg m −3 ) significantly on day 5. Gibberellin and citrate augmented the biomass by 0.935 kg m −3 and 1.025 kg m −3 . Combination of CGF and phytohormones were more effective than CGF and carbon sources. Analysis of fatty acid methyl esters indicated that the ratio of saturated to unsaturated fatty acids is higher in cytokinin, abscisic acid and CGF, and are also rich in short chain carbon atoms, ideal criteria for biodiesel. Nitrogen starvation favoured synthesis of more unsaturated fatty acids than saturated. This study shows that CGF enhances the biomass and lipid significantly and thus can be used for large scale biomass production. Highlights: Optimization studies revealed 7th day to be the ideal period for harvesting Chlorella vulgaris . Chlorella growth factor extract acted as a chief growth promoting factor of C. vulgaris . Chlorella growth factor with carbon sources or phytohormones was not effective than chlorella growth factor extract alone. Cytokinin treatment increased saturated fatty acids level, although the biomass production was not significant.